Impulsive Buying in Early Adulthood in Terms of Gender - Fransiska Dian Puspitayanti; Apris A. Adu; Dian L. Anakaka (Journal of Health and Behavioral Science, 2022)
Individuals, of course, must meet their needs to survive. Ways to meet needs can come in the form of buying something or creating something. Many daily shopping activities are based on something other than careful consideration. This is called impulse buying. The hypothesis in this study is that there are gender differences in impulse buying in early adulthood in Kupang City. The participants in this study were the people from Kupang City in their early adulthood who made purchases in Kupang City, a total of 400 respondents. The sampling technique used was random sampling. The data collection technique used the Impulsive Buying Tendency Scale (IBTS), which consisted of 16 items. Data analysis used the Mann-Whitney U-test. This study concluded that there was a significant difference in impulsive buying behavior in early adulthood in Kupang City in terms of gender, with the analysis of the average score of female impulsive purchases being greater than that of males with a significant level of 0.005.